ANALISIS MAJAS SINDIRAN DAN KESANTUNAN BERBAHASA DALAM DEBAT KEEMPAT CALON WAKIL PRESIDEN PEMILU 2024 - Yenny Lusianasari; Agus Darmuki; Muhammad Noor Ahsin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the use of satire and politeness in the 2024 Vice PresidentialCandidate debate using qualitative methods. The theory used for the satire aspect isKeraf's theory, and for the politeness aspect, Leech's theory. The data collectiontechnique used was listening and note-taking. The results of this study indicate that thedebate still contained the use of satire and the use of politeness was still lacking. This isevidenced by the results of the satire data, which produced 18 data points, and thepoliteness data, which produced 38 data points.